2011
DOI: 10.5194/acpd-11-22663-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing regional scale predictions of aerosols, marine stratocumulus, and their interactions during VOCALS-REx using WRF-Chem

Abstract: In the recent chemistry version (v3.3) of the Weather Research and Forecasting (WRF-Chem) model, we have coupled the Morrison double-moment microphysics scheme with interactive aerosols so that two-way aerosol-cloud interactions are included in the simulations. We have used this new WRF-Chem functionality in a study focused on assessing predictions of aerosols, marine stratocumulus clouds, and their interactions over the Southeast Pacific using measurements from the VAMOS Ocean-Cloud-Atmosphere-Land Study Regi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 59 publications
3
43
0
Order By: Relevance
“…In this sense, it is encouraging that for a given region, a single formula can be used across satellites and instruments (GOES imager, MODIS Aqua, and Terra) with excellent performance against N d in situ data, remarkably better than for other retrieved cloud properties (28,35). The activation parameterization and its assumptions represent another source of uncertainty (20), but again, comparisons with in situ and satellite measurements help better understand these limitations and their extent (6,7). Expanded applications of this approach (e.g., aerosol retrieval and assimilation under multilayer, convective, and ice clouds) may be possible, but additional research and testing is required on both retrieval and modeling sides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, it is encouraging that for a given region, a single formula can be used across satellites and instruments (GOES imager, MODIS Aqua, and Terra) with excellent performance against N d in situ data, remarkably better than for other retrieved cloud properties (28,35). The activation parameterization and its assumptions represent another source of uncertainty (20), but again, comparisons with in situ and satellite measurements help better understand these limitations and their extent (6,7). Expanded applications of this approach (e.g., aerosol retrieval and assimilation under multilayer, convective, and ice clouds) may be possible, but additional research and testing is required on both retrieval and modeling sides.…”
Section: Discussionmentioning
confidence: 99%
“…Despite uncertainties (10) and challenges (20) in modeling aerosol-cloud interactions, recent studies have shown significant capabilities in predicting and explaining aerosol indirect effects in low cloud regimes (6,7,21). By building on this mechanistic understanding, observations of clouds may be used to infer aerosol physicochemical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fully coupled on-line models, where meteorological and chemical processes are solved together on the same grid and with the same physical parameterizations are able to simulate the complex aerosol-cloud-radiation feedback effects (Zhang, 2008). Recent case studies have shown that the inclusion of feedback effects can improve the model performance for specific cases and conditions Bangert et al, 2012;Yang et al, 2011;Forkel et al, 2012). More research and studies are needed to investigate how the inclusion of feedback effects within on-line air quality models affects the simulation results over Europe for a longer simulation episode.…”
Section: Introductionmentioning
confidence: 99%
“…Realistic simulation of the feedback effects requires the use of integrated meteorology-chemistry on-line models that include detailed treatment of aerosol life cycle and aerosol impacts on radiation (direct effects) and clouds (indirect effects) (Baklanov et al, 2014;Baklanov, 2011, Bangert et al, 2012;Yang et al, 2011). Historically, the study of these effects has been done separately in modeling approaches.…”
Section: Introductionmentioning
confidence: 99%